Indoor Positioning System Based on UWB Rapid Integration with Unity Cross Platform Development Engine through IoT - Zikrul Hakiem Ishak; Sallehuddin Mohamed Haris (Journal of Artificial Intelligence and Technology, 2024)
The changes in time have made divergences of endless possibilities in localization technology. Localization in an indoor environment is surely a concerning matter as several shortcomings always arise when dealing with indoor localization. To optimize localization in an indoor environment, tracking a subject’s position in real-time is a certainly vital interest. Challenges in obtaining an accurate position in precise millimetre accuracy whilst the subject perceive visual information rendered in real-time is somewhat always a matter in hand to address in an indoor environment. The main objective of this research is to implement a positioning method in an indoor environment base on ultra-wideband (UWB) technology to obtain position accuracy in millimetres by rapidly integrating with Unity three-dimensional (3D) engine hence obtaining a detailed inertial measurement unit (IMU) data via wireless Message Queuing Telemetry Transport (MQTT) network protocol. The key results of this research should ensure an establishment of an indoor positioning system based on providing the finest selection of positioning and UWB parameters. These fine selections are an important design choice impacting the system’s performance in obtaining an accurate position within the range of 0.15mm to 115mm. The technological benefits involve the innovation of wireless communication based on the internet of things (IoT) concept relevant to the Industrial Revolution 4.0 (IR 4.0) enabling participants to move freely in an indoor environment whilst obtaining accurate and precise positioning coordinates. Future recommendations comprise of real-time two-dimensional (2D) Pozyx Creator Controller integrated with Unity 3D user graphical user interface (GUI) purposes intended for mobile mapping navigations.